Islamic natural law theories - Emon, Anver M. (Oxford : Oxford University Press, 2010)
This text offers a sustained jurisprudential inquiry into Islamic natural law theory. It introduces readers to the central figures in the Islamic natural law tradition and their canonical works, analyses the historical development of Islamic jurisprudence and explains the major contrasts with Western traditions of natural law.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Islamic law; Natural law -- Religious aspects -- Islam